Traditions and Cultural Heritage: Genesis, Reproduction, and Preservation - Holl, Augustin F. C. (Traditions and Cultural Heritage: Genesis, Reproduction, and Preservation, 2023)
The contributions assembled in this volume are the products of an intensive graduate seminar with a strong and practical focus on writing. Methodologies discourses and advices, useful as they can be have limited practical impacts. One learns how to write by writing, over and over again. Accordingly, as the seminar name “Writing Anthropology” suggests was designed through weekly written and oral exercises to practice research writing based on current standard. It is however, the teaching methodology set in place to achieve the formulated goal that set this experiment aside. The pedagogy set in place in this project empowers graduate students, through implementation of mechanisms of collective decision-making. The students are the one making decision about the research themes to be investigated during the whole semester. Each student anonymously suggests a theme. The suggested themes are then listed alphabetically with their frequency of iteration and returned to the students to craft a short list and narrow the range of choices. The student body of that semester decided to focus on a combination of two themes addressed from China perspective: traditions and cultural heritage in anthropological perspectives. Harnessing tools from archaeology, linguistics, and cultural anthropology, the contributions examine the genesis, reproduction, and preservation of these fragile treasures of human mind.